2011
DOI: 10.1007/s00415-011-6191-x
|View full text |Cite
|
Sign up to set email alerts
|

Emotional adjustment in amyotrophic lateral sclerosis (ALS)

Abstract: Despite the devastating motor impairment, a significant number of patients with amyotrophic lateral sclerosis (ALS) maintain a good psychosocial adjustment. Here we investigated whether this is specific for ALS or a more general characteristic of terminal disease. Psychosocial adjustment was investigated in 30 ALS patients, 29 cancer patients in palliative treatment and 29 age-, gender- and level of education-matched healthy controls. Subjective quality of life (sQoL), degree of depressive symptoms and coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…This could also explain the fact that only 9% of the older patients used antidepressants compared with 58% of the younger patients. Good psychosocial adaption to severe chronic disease has also been observed in patients in the final palliative stages of cancer and in locked-in patients after stroke [22] . Still, although the younger group contained more patients who would retrospectively not give consent, the overall acceptance for DHC is high.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This could also explain the fact that only 9% of the older patients used antidepressants compared with 58% of the younger patients. Good psychosocial adaption to severe chronic disease has also been observed in patients in the final palliative stages of cancer and in locked-in patients after stroke [22] . Still, although the younger group contained more patients who would retrospectively not give consent, the overall acceptance for DHC is high.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings indicate that the preparedness to be content to be alive and to accept disability seems to be higher among older patients. Studies of QoL associated with other severe diseases such as amyotrophic lateral sclerosis showed that a high level of previous health and a short time for adaptation lead to lower levels of QoL and acceptance of disability [22] . The fact that elderly patients already have experienced a higher burden of chronic disease may help them develop better disease acceptance than younger subjects whose condition has changed rapidly from good health to a severely disabled state.…”
Section: Discussionmentioning
confidence: 99%
“…Of greater importance appears to be the tendency of ALS patients to actively negate the disease, so relegating it out of conscious awareness (Brown and Mueller, 1970; Grossman et al, 2006). In ALS, the so-called ‘ disability paradox’ concerns evidence that subjective QoL and emotional well-being in ALS patients are comparatively good and partially unrelated to physical functioning and disease severity and progression (Kurt et al, 2007; Lulé et al, 2008, 2012; Norris et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…At home, particular attention is placed to family dynamics; the intervention here is characterized by the creation of a proper setting. In Help Groups the psychologist focuses on the resources of each participant; coping strategies [29] are shared among the participants to face distress and to create a networking against existential isolation [18][19][20][21][22][23][24][25][26][27][28][29][30]. During the last decade, attention to psychological approach in neuromuscular diseases increased [31], nevertheless a definite model of intervention is absent and there is a lack of guidelines in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological intervention during the progression of the disease consists in one or more psychoeducational sessions, psychological support and mediation. The aim is to restrain the distress and to reinforce the resources of the context [17][18][19][20][21].…”
Section: It Is Recommended To Plan Periodical Meetings With the Care mentioning
confidence: 99%